THE RELATIONSHIP OF SERVICE QUALITY, TRUST, AND SATISFACTION OF MUSLIM PATIENTS IN ARAFAH ISLAMIC HOSPITAL JAMBI WITH ISLAMIC ECONOMIC APPROACH - RIDHWAN RIDHWAN; LUCKY ENGGRANI FITRI; RACHMAT HIDAYAT (Universitas Islam Negeri Imam Bonjol Padang, 2019)
This study aimed to know the direct effect of service quality, on the satisfaction and trust of Muslim patients in Arafah Islamic hospital in Jambi city. The design of this study used a quantitative method with a survey approach to obtain primary data, namely by distributing questionnaires to 140 inpatients in Arafah Islamic hospital in Jambi city using the purposive sampling method. Then quantitative data was processed using Structural Equation Model (SEM) with the application of SmartPLS 3. The results of this study indicated that service quality has a significant effect on satisfaction and trust, as well as satisfaction has a significant effect on trust. This research was expected to make a practical contribution to management of Islamic hospital for an effort to increase patient satisfaction and trust.